(3NdGUI GdCbhGd aj eYQaI GdQLGds - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3eMeO fUjQ Hf Cejf GdOjf GdfLajs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEJ GdYde HMGd GdQhGI ef CSGS GdGMcGe GdTQYjI hYdjg JHfi GdbhGYO GdSeYjI jLH Ydi cd eLJgO eYQaJg hYdeg adG jShZ dg JQcg hLgdg (B...s
(3BNQgG (B:s
... (3hHgPG GdESfGO Yf CHj GdUeUGe Yf GdfLGTj HcJGHg hHGdESfGO Yf GdTjN CHj LYaQ GdWhSj Yf CHj eMeO gGQhf Hf ehSi GdJdYcHQj Yf CHj YeQh eMeO Hf YeQ Hf YHO GdYRjR (B... (3hGdMeO ddg hMOgs
(3JHUQI GdeDda (B:s
(3UGMH cJGH (B: (3cTa GdebGd aj eYQaI GdQLGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B2/227s
(3EjVGM Gdecfhf (B1/433s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs